CAD - CAM in Pediatric Dentistry: A brief insight (Bangladesh Journal of Medical Science, 2024)
On introduction of computer aided technology/computer aided manufacturing in pediatric dentistry, treating children has become effortless, mainly children with special health-care needs. This technology aims at the fabrication of restorations with higher strength and better aesthetics by an effortless, quicker and more precise operational process. This technology has proved to be a boon in various fields in pediatric dentistry. The latest trend of minimally invasive dentistry, relies on selective caries removal and restoring it with material which is highly adhesive and aesthetic. CAD-CAM makes use of an optical impression of the required area and occlusion which is taken using hassle-free intra-oral scanners. Machinable high strength composite/ceramic blocks are used which can be polymerized under pressure and temperature. The CAD-CAM technology has its advantage of needing less chair side time, brisk production of restorations with increased precision, eliminating the need for classic methods of impression, high strength and aesthetic restorations and prostheses. CAD-CAM technology can be used for smile designing in patients with developmental defects like Amylogenesis Imperfect, Molar-Incisor Hypo mineralization, etc., prosthetic rehabilitation in patients’ requiring stainless steel crowns and zirconia crowns, restorative procedures like inlays and onlays, naso-alveolar molding etc. Thus, it opens up a sea of possibilities for providing a high quality of treatment for the child with minimal hassle and maximal benefits to the child.Bangladesh Journal of Medical Science Vol.23 (Special Issue) 2024 p.S38-S42